DIFFERENCES BETWEEN ENGLISH AND UZBEK IN LEARNING (Ustozlar uchun, 2025)
Introduction: English has become a global language, essential for education, business, and international communication. However, for Uzbek learners, mastering English is not always easy because the two languages are very different in their structure, grammar, and pronunciation. English belongs to the Germanic branch of the Indo-European language family, while Uzbek is part of the Turkic family. This means that they have little in common, and learners often face challenges when moving from one system to the other. By analyzing the main differences—such as word order, articles, verb tenses, and pronunciation—students can better understand the difficulties they face and find more effective strategies for learning English.